Economic evaluations of strategies targeting pre-diagnosis dementia populations: Protocol for a systematic review [version 2; peer review: 2 approved, 1 approved with reservations] - Alina Zenker; Men Thi Hoang; Ulf-Göran Gerdtham; Sanjib Saha; Dominic Trepel (HRB Open Research)
Introduction Dementia remains incurable, and treatment trials are typically conducted after the symptoms manifest, potentially too late in the disease process to alter its course. Early identification and intervention during the pre-diagnosis phase offer the potential to introduce more cost-effective strategies and enhance quality of life. This review aims to scrutinise emerging evidence and present a comprehensive summary of cost-effectiveness estimates of all strategies targeting the pre-diagnosis dementia population. Method and analysis A systematic search will be conducted across six electronic databases. All articles will be assessed against pre-defined eligibility criteria through title and abstract screening, and full-text screening phases. Data from the included articles will be extracted using a standardized template. A newly established framework based on the CHEERS 2022 checklist will be applied to assess the reporting quality of the included articles. The entire review process, from screening to data extraction and quality assessment, will be a dual process conducted by two reviewers. Disagreements will be resolved by a third senior reviewer. The extracted data will be synthesised and presented in tables and figures. Conclusion This systematic review will present evidence of cost-effectiveness, along with the strengths and limitations of the existing literature. These findings aim to identify existing gaps, thereby informing and guiding the design of future studies in this domain. Ethics and dissemination Since this is a systematic review protocol, ethical approval is not required. The results will be published in a peer-reviewed journal, with both raw and summarised data shared through the journal or other open platforms. Systematic review registration PROSPERO - CRD42024521521.